Minimal hypersurfaces with low index in the real projective space. (May 2022) - Batista, Márcio; Martins, Matheus B.
Abstract: In this paper we use suitable ideas from the min–max theory in finite dimension to prove that the only compact two-sided minimal and constant scalar curvature hypersurfaces in the real projective space with Morse index less or equal to two are the totally geodesic sphere or the Clifford minimal hypersurfaces.